ANALISIS KINERJA KANTOR UNIT BANK RAKYAT INDONESIA (BRI) CABANG MEULABOH MELALUI PENDEKATAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Arie Saputra (Jurnal Optimalisasi, 2016)
Efficiency is one of the important performance indicators in measuring the performance of an organization, determination of process efficiency by comparison to some of the units of measurement into a proportional response to the question of overall performance object pengmatan unit. This study aims to determine the value of the relativity of a banking organization's efficiency through approaches diunit Data Envelopment Analysis (DEA). Values relative efficiency of a unit obtained by the ratio of input and output used to see the amount of weight of each unit when there is a process of comparison (benchmarking). Adapaun data used in this study are primary data derived from Bank BRI branch office unit that Meulaboh Cut Nyak Dien office units, office units and office units Johan Pahlawan Teuku Umar in the form of annual financial reports for two years (2014 and 2015). For the study variables divided into two input variables consisting of the number of employees, the number of deposits, the number of customers and the amount of operating costs (BOP) while the output variable is the number of loans and total income (revenue). By using the DEA method can know the amount of the value of the relative efficiency of the three units of Bank BRI branch offices in Meulaboh, for the year 2014 Cut Nyak Dien office units, office units and office units Johan Pahlawan Teuku Umar obtain efficient relative value = 1, which means efficient. Whereas in 2015 the office unit Johan Pahlawan obtain the relative efficiency value = 0.81, which means less efficient. In order to achieve the level of efficiency relative = 1, then the office of Johan Pahlawan unit should increase the number of variables output by 41.18%. where an increase in the output variable Johan Pahlawan office unit for the amount of credit granted is Rp. 910 515 743 and for the income (revenue) amounting to Rp. 2738029201.Keywords : Bank Performance, Data Envelopment Analysis (DEA), relative efisiensi.